2019
DOI: 10.1029/2019gl082114
|View full text |Cite
|
Sign up to set email alerts
|

Buried Ice and Sand Caps at the North Pole of Mars: Revealing a Record of Climate Change in the Cavi Unit With SHARAD

Abstract: The cavi unit at the north pole of Mars is a deposit of aeolian sand and water ice underlying the Late Amazonian north polar layered deposits. Its strata of Middle to Late Amazonian age record wind patterns and past climate. The Mars Reconnaissance Orbiter Shallow Radar (SHARAD) reveals extensive internal and basal layering within the cavi unit, allowing us to determine its general structure and relative permittivity. Assuming a basalt composition for the sand (ε′ = 8.8), results indicate that cavi contains an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 55 publications
1
53
0
Order By: Relevance
“…The inferred compositions suggest that there must be at least 10 vol% of solid CO 2 (0.15 to 0.17 × 10 6 km 3 , 59 to 67 mbar) within the polar cap if the dust content is larger than 6 vol%, as suggested by the radar estimates of Nerozzi and Holt (2019), the rest being water ice. Increasing the dielectric constant of water ice (from 3 to 3.15, e.g., Grima et al, 2009) or that of the dust (from 6 to 8.8, e.g., Nerozzi & Holt, 2019), or adding more dust to the polar cap, would require an even larger solid CO 2 content.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The inferred compositions suggest that there must be at least 10 vol% of solid CO 2 (0.15 to 0.17 × 10 6 km 3 , 59 to 67 mbar) within the polar cap if the dust content is larger than 6 vol%, as suggested by the radar estimates of Nerozzi and Holt (2019), the rest being water ice. Increasing the dielectric constant of water ice (from 3 to 3.15, e.g., Grima et al, 2009) or that of the dust (from 6 to 8.8, e.g., Nerozzi & Holt, 2019), or adding more dust to the polar cap, would require an even larger solid CO 2 content.…”
Section: Discussionmentioning
confidence: 79%
“…• Supporting Information S1 of dust (Herkenhoff et al, 2007;Nerozzi & Holt, 2019). Both MARSIS and SHARAD observed a general lack of downward deflection below the north polar cap with uncertainties of about 200 m everywhere (Selvans et al, 2010) and 100 m across Gemina Lingula (Phillips et al, 2008) (Figure 1).…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, radar investigations found little attenuation of the radar signal by the BU suggesting that it may only contain a few percent contaminants mixed with water ice (Selvans et al, 2010). Further work by Lauro et al (2012) and Nerozzi and Holt (2019) have both found evidence for significantly more contaminants in some parts of the BU. Nerozzi and Holt (2019) used SHARAD data to reveal substantial spatial variations in the bulk dielectric constant of the cavi unit in PB and Olympia Planum.…”
Section: 1029/2019gl082294mentioning
confidence: 95%
“…We would like to thank Dr. Steven Hauck II for his assistance with the computation. The radar data used in this work are a published database that may be obtained from Nerozzi and Holt () (https://agupubs.onlinelibrary.wiley.com/doi/10.1029/2019GL082114). No other data are generated as part of this work.…”
Section: Acknowledgmentsmentioning
confidence: 99%